2012
DOI: 10.1007/s10646-012-0884-5
|View full text |Cite
|
Sign up to set email alerts
|

Coelomic fluid: a complimentary biological medium to assess sub-lethal endosulfan exposure using 1H NMR-based earthworm metabolomics

Abstract: Endosulfan is an environmentally persistent pesticide and has been shown to be genotoxic, neurotoxic and carcinogenic to surrounding organisms. Earthworms are widely used in environmental metabolomic studies to assess soil ecotoxicity. Previous nuclear magnetic resonance (NMR)-based metabolomic studies have analyzed earthworm tissue extracts after exposure to endosulfan and identified some key metabolic indicators that can be used as biomarkers of stress. However, some metabolites may have been masked due to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
4
19
0
Order By: Relevance
“…Communications nearly identical to that of the aqueous buffer extract. [24] It also confirms that the real line-shape,p eak intensities,a nd the general spectra profile are well represented in the IP-iSQC. (a perfect correlation should not be expected, as as eparate worm was used to prepare the buffer extract.…”
Section: Angewandte Chemiesupporting
confidence: 67%
See 1 more Smart Citation
“…Communications nearly identical to that of the aqueous buffer extract. [24] It also confirms that the real line-shape,p eak intensities,a nd the general spectra profile are well represented in the IP-iSQC. (a perfect correlation should not be expected, as as eparate worm was used to prepare the buffer extract.…”
Section: Angewandte Chemiesupporting
confidence: 67%
“…[24] It also confirms that the real line-shape,p eak intensities,a nd the general spectra profile are well represented in the IP-iSQC. [24] It also confirms that the real line-shape,p eak intensities,a nd the general spectra profile are well represented in the IP-iSQC.…”
supporting
confidence: 69%
“…CF was extruded from the earthworms similarly to previously described methods. 7 , 12 Earthworms were dipped in EMD Millipore Simplicity ultrapure water to remove soil and patted dry. The earthworm was transferred to a 35 × 10 mm Falcon Petri dish containing 500 μL of 0.1% NaCl in ultrapure water.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolomic impact of endosulfan on the CF and whole-tissue extract of E. fetida was measured via the Organization for Economic Co-operation and Development (OECD) filter paper test. 12 Decreases in α-ketoglutarate, malate, spermidine, and succinate were observed in the tissue and CF of exposed worms, while alanine, ATP, betaine, lactate, and myo -inositol levels increased. In the whole-worm extract, fumarate also decreased in comparison with the control.…”
Section: Introductionmentioning
confidence: 95%
“…Two earthworm species, Eisenia fetida and Eisenia andrei , have been used in European pesticide marketing authorization experiments since the early 1980s [ 6 ]. In these studies, several bioactive proteins were identified in the coelomic fluid of earthworms [ 7 9 ]. These proteins exhibit a variety of antibacterial, hemolytic, cytotoxic, hemagglutinating, and proteolytic activities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%